Technical efficiency and its determinants: Paddy farming in Mahakanumulla cascade system - Perera, K.L.P.A.; Hemachandra, D. (University of Jaffna, 2021)
Paddy farming is predominantly practiced in the dry zone of Sri Lanka. Most paddy lands in the dry zone belong to traditional hydrological cascade systems known as Village Tank Cascade Systems (VTCS) and paddy lands receive irrigation water from the tanks in VTCS. Land is a scarce resource for agriculture in Sri Lanka. Therefore, it is important to achieve high efficiency in paddy farming to increase paddy production in the country. A paddy farm is technically efficient if it is producing the maximum output using the minimum quantities of inputs, such as labour, capital, and technology. This study examines technical efficiency of paddy farmers in Mahakanumulla VTCS and its determinants. The technical efficiency of the farmers is estimated using parametric frontier technique; the Stochastic Frontier Analysis (SFA). In the first stage of the analysis a production function is estimated using the Maximum Likelihood Estimator. In the second stage, an inefficacy model is estimated with plot size, age,experience, household size, full time farming, and land ownership status as determinants of technical inefficiency. According to the results, the average technical efficiency of paddy farmers in Mahakanumulla VTCS is 92.3%. Only the plot size, experience, and household size are positively related to technical inefficiency and significant at 10%. According to the study findings, the technical efficiency of paddy farmers in Mahakanumulla VTCS does not vary significantly from the most efficient farmer in the area. This could be due to the fact that in the VTCS, farmers are operating under more homogenous conditions. However, it does not indicate that paddy farmers in Mahakanumulla VTCS are highly productive as results only reveal the technical efficiency level of paddy farmers in comparison to the most efficient paddy farmer in the area. Therefore, it is important that productivity improvements are continuously carried out.
Keywords: Inefficiency model; Land tenure; Paddy; Stochastic frontier analysis; Technical efficiency